Endoscopic Third Ventriculostomy in Cases of Hydrocephalus: An Institutional Experience - Saxena, Prarthana; Pandey, Sharad; Kumar, Pankaj; Kausik, Kaviraj; Soni, Shiv Lal (Indian Journal of Neurosurgery, 2019)
Background With the recent advances in optical and mechanical instrumentation, endoscopic third ventriculostomy (ETV) has emerged as the procedure of choice for the treatment of hydrocephalus in selected patients.Objective: To study the role of ETV in therapeutic management of hydrocephalus in a tertiary care center.Materials and Methods The present study was conducted in the Department of Neurosurgery at Dr. Ram Manohar Lohia Hospital. Endoscopic third ventriculostomy was performed as a therapeutic procedure in patients diagnosed with hydrocephalus requiring surgical intervention and admitted from June 2017 to July 2018. ETV success was defined by resolution or improvement in clinical symptoms and ETV failure was considered in patients whose symptoms either deteriorated or did not improve from the baseline and required ventriculoperitoneal shunt.Results A total of 85 patients were included in this study who underwent the therapeutic ETV. In the present study, the overall ETV success rate was 75.2% (64/85). 86.7% cases of aqueductal stenosis, 74.4% cases of post meningitis (including tubercular meningitis) hydrocephalus, and 71% of posterior fossa tumors showed resolution or improvement in clinical symptoms.Conclusion ETV is an effective treatment modality for obstructive hydrocephalus and with better results in post meningitis hydrocephalus and post tubercular meningitis hydrocephalus. However, more extensive studies dedicated to ETV with a larger sample size are required to further study its efficacy in various etiologies.
Keywords: endoscopic third ventriculostomy; hydrocephalus; ETV success